Traditional risk factors and premature acute coronary syndromes in South Eastern Europe: a multinational cohort study - Bugiardini, Raffaele; Cenko, Edina; Yoon, Jinsung; Bergami, Maria; Vasiljevic, Zorana; Mendieta, Guiomar; Zdravkovich, Marija; Vavlukis, Marija; Kedev, Sashko; Miličić, Davor; Badimon, Lina; Manfrini, Olivia (Elsevier BV, 2024)
The age-standardized death rates under 65 years from ischemic heart disease in South Eastern Europe are approximately twice as high than the Western Europe average, but the reasons are not completely recognized. The aim of the present study was to address this issue by collecting and analyzing data from a large, multinational cohort.
Keywords: Ischemic heart disease; Risk factors; Sex differences